Corsarios franceses juzgados como herejes luteranos por la inquisición en Iberoamérica, 1560-1574 - Ruiz Martínez, Herlinda (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
During the XVI century, the presence of some foreigners in lands belonging to the Spanish empire, in the New World, mainly corsairs and pirates of English and French origin whose religion was the Anglican one and the Calvinist, for divergent ende of the Catholic, prevailing in the Spanish metropolis and its territories in the New World, added to violations that some bishops made invested with inquisitorial powers who imparted justice between 1517 and 1569, before the Tribunal was formally established in the Spanish American viceroyalties, they were reasons so that the ecclesiastical authorities of Mexico and Lima requested the Spanish king Felipe II the foundation of the Saint's Occupation Tribunal in Latin America, with the purpose of controlling these abuses. On the other hand, to the Hispanic king it interested him/her very much to avoid the diffusion of the Lutheran ideas and Calvinists to play regions belonging to Spain. The arrival and permanency of a group of more than 100 Englishmen in New Spain in September of 1568,1 seems to have influenced the since sovereign's decision, for January 25 15692 it would order the establishment of the inquisitorial tribunals with headquarters in the capitals of the viceroyalties of Peru and New Spain.

Durante el siglo XVI, la presencia de algunos extranjeros en tierras pertenecientes al imperio español, en el Nuevo Mundo, principalmente corsarios y piratas de origen inglés y francés, cuya religión era la anglicana y la calvinista, por ende divergentes de la católica, imperante en la metrópoli española y sus territorios en el Nuevo Mundo, sumada a atropellos que cometían algunos obispos investidos con poderes inquisitoriales, quienes impartieron justicia entre 1517 y 1569, antes de que el Tribunal fuera formalmente establecido en los virreinatos hispanoamericanas, fueron motivos para que las autoridades eclesiásticas de México y Lima solicitaran al monarca español Felipe II la fundación de un Tribunal del Santo Oficio en Iberoamérica, con el fin de controlar estos abusos. Por su parte, al rey hispano le interesaba muchísimo evitar que la difusión de las ideas luteranas y calvinistas tocara regiones pertenecientes a España. La llegada y permanencia de un grupo de más de 100 ingleses en la Nueva España en septiembre de 1568,1 parece haber influenciado la decisión del soberano pues, para el 25 de enero de 15692 ordenaría el establecimiento de los tribunales inquisitoriales con sede en las capitales de los virreinatos del Perú y la Nueva España.
Instituto de Investigaciones Históricas. Facultad de Historia. Programa Institucional de Maestría en Historia
Keywords: info:eu-repo/classification/cti/4; IIH-M-2011-0005; Opción en historia de América; Corsarios franceses; Herejes luteranos; Inquisición; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2404